DAMPAK GAME ONLINE TERHADAP HASIL BELAJAR PADA MATA PELAJARAN SEJARAH DI SMA N 4 KOTA JAMBI TAHUN AJARAN 2021-2022 - Armando, Imandestario Dwi; Agustiningsih, Nur (Universitas Batanghari Jambi, 2022)
This study aims to see how big the impact of online games on student learning outcomes in history subjects at SMA N 4 Jambi City Academic Year 2021-2022. In this study using descriptive qualitative research methods with percentage analysis, data collection researchers used interview questionnaires to collect student data and for data collection of students' academic scores using the goggle form through random sampling techniques, by obtaining value data for playing online games by not playing online games, data processing techniques using world percentages, based on the results of research that has been researched for approximately two month, That the number of students who play online games is 80% of the 60 students as respondents and above the KKM as many as 85% of students from 48 respondents who play online games, while those who do not play online games are 15% of 60 respondents . The researcher concludes that students who play online games can be said to be low, that online games have no impact on students' history lessons at SMAN 4 Jambi City and only have an impact of 7% of students on learning outcomes in history subjects.